Tanggap Kedelai Hitam terhadap Cekaman Aluminium pada Kultur Hara - Pujiwati, Hesti; Ghulamahdi, Munif; Yahya, Sudirman; Aziz, Sandra Arifin; Haridjaja, Oteng (Pusat Penelitian dan Pengembangan Tanaman Pangan, 2016)
Al-stress on soybean causes inhibited root growth. Root length sensitivity index might be an indicator of roots tolerance to Alstress. Hematoxylin staining can be used to visualize the movement of Al in plant root tissues. This study was aimed to determine the tolerance level of soybean genotypes to the gradual Al concentrations. The experiment was conducted from February to April 2014, at the greenhouse in Cikabayan Experiments Garden, IPB, using a 4 x 3 factorial treatments in a completely randomized design, three replications. The first factor was the concentration of Al ie: without Al (A0); 0.5 mM Al (A1); 0.7 mM Al (A2) and 0.9 mM (A3). The second factor was the soybean varieties including: Tanggamus, Cikuray, and Ceneng. The observation of variable included root length sensitivity index based on hematoxylin staining, demonstrating the movement of Al on the tolerance and sensitive varieties. Results showed that: 1) Tanggamus was tolerance at 0.5 mM Al concentration and was moderate at 0.7 and 0.9 mM Al, 2) Cikuray was tolerance to a concentration up to 0.5 mM and was moderate at 0.7 mM Al but was sensitive to the concentration of 0.9 mM Al, 3) Ceneng was sensitive at concentration of 0.5 to 0.9 mM Al, 4) Staining hematoxylin indicated the root tissue advanced damages and darker blue color on the susceptible varieties, in comparison with the tolerant ones.